Artificial Feeding for Severely Disoriented Elderly - McAlister, Neil H. (1989)
The issue of artificial feeding for patients with dementia who refuse feeding by hand is a wrenching emotional problem that can cloud clinical judgement. It is helpful to apply an analytic approach to decision making. There are five steps: gathering a comprehensive clinical database; defining the goal of treatment; knowing the treatment options available, their burdens and potential benefits; understanding the law; and defining the moral framework in which care is being given. Such an approach can be used to formulate a plan of treatment in the best interests of incompetent elderly patients who cannot speak for themselves.